2018
DOI: 10.1007/s00167-018-5095-z
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term clinical and radiological results do not differ between fixed- and mobile-bearing total knee arthroplasty using titanium-nitride-coated posterior-stabilized prostheses: a prospective randomized controlled trial

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…There are several limitations to this study, most importantly, the low number of examined components with a relatively short in vivo service time. It is very difficult to collect such retrievals because TiN coated implants are not routinely used in large groups of patients (Breugem et al, ; Buechel Sr et al, ; Buechel Sr et al, ; Park et al, ; Thienpont, ; Van Hove et al, ). This is reflected by lack of registry data and a small body of literature regarding Ti(Nb)N coated arthroplasties, and retrieval studies focused on such implants also involved small sample numbers (Bone & Naylor, ; Fabry et al, ; Harman et al, ; Khatkar et al, ; Łapaj et al, ; Łapaj, Markuszewski, et al, ; Malviya et al, ; Raimondi & Pietrabissa, ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There are several limitations to this study, most importantly, the low number of examined components with a relatively short in vivo service time. It is very difficult to collect such retrievals because TiN coated implants are not routinely used in large groups of patients (Breugem et al, ; Buechel Sr et al, ; Buechel Sr et al, ; Park et al, ; Thienpont, ; Van Hove et al, ). This is reflected by lack of registry data and a small body of literature regarding Ti(Nb)N coated arthroplasties, and retrieval studies focused on such implants also involved small sample numbers (Bone & Naylor, ; Fabry et al, ; Harman et al, ; Khatkar et al, ; Łapaj et al, ; Łapaj, Markuszewski, et al, ; Malviya et al, ; Raimondi & Pietrabissa, ).…”
Section: Discussionmentioning
confidence: 99%
“…Coating wear and presence of defects could also negatively affect tribological properties of the implants, potentially accelerating polyethylene wear and osteolysis (Wang, Polineni, Stark, & Dumbleton, ). Nonetheless, data from studies published so far did not demonstrate increased failure rates for TiN coated TKRs, and a study by Fabry et al suggested that TiN coated femoral components are more scratch resistant than oxidized zirconia films and conventional CoCrMo components which could minimize topside wear (Breugem et al, ; Fabry et al, ; Park et al, ; Thienpont, ; Van Hove et al, ). In the present study, femoral components of TKRs and UNIs had lower damage scores and fewer microscopic signs of wear than tibial components, suggesting that application of TiN coatings may potentially minimize topside wear in total and partial knee replacements, but has a limited effect on wear of the tibial mobile bearings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations